Pengaruh Sosial Media Tiktok dan Word Of Mouth Terhadap Keputusan Pembelian Produk Skincare G2glow - Noviana, Anisa; Marwansyah, Sofyan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to determine the influence of TikTok media social and Word of Mouth (WOM) on purchasing decisions for G2Glow Skincare products. The research background is based on the increasing use of TikTok as an interactive promotional medium capable of reaching a wide audience, as well as the importance of WOM, which is considered more credible by consumers than traditional advertising. This study employs a quantitative method with a population consisting of G2Glow consumers who are active on TikTok and have previously made a purchase. The sample consisted of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression, including validity and reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results show that TikTok social media has a positive and significant effect on purchasing decisions, with a t-value of 6.498 > t-table 1.984. WOM also has a positive and significant effect, with a t-value of 3.864 > t-table 1.984. Simultaneously, both variables significantly influence purchasing decisions, with a determination coefficient of 39.7%. These findings confirm that marketing strategies through creative, relevant, and consistent TikTok content, supported by positive WOM, can enhance consumer interest and purchasing decisions